Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1968
DOI: 10.1152/ajplegacy.1968.215.4.889
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic transmission of antral slow waves across the gastroduodenal junction in situ

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

1970
1970
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 0 publications
3
20
1
Order By: Relevance
“…The pattern of spontaneous electrical activities of the antrum muscle fibers was similar to those of mammalian stomach muscles recorded by previous investiga tors (Ichikawa and Bozler 1955;Papasova et al 1968;Bortoff and Davis 1968;Fujii 1971), particularly those recorded intracellularly (Kuriyama et al . 1970;Ito and Kuriyama 1975).…”
Section: Discussionsupporting
confidence: 79%
“…The pattern of spontaneous electrical activities of the antrum muscle fibers was similar to those of mammalian stomach muscles recorded by previous investiga tors (Ichikawa and Bozler 1955;Papasova et al 1968;Bortoff and Davis 1968;Fujii 1971), particularly those recorded intracellularly (Kuriyama et al . 1970;Ito and Kuriyama 1975).…”
Section: Discussionsupporting
confidence: 79%
“…Only the occurrence of action potentials in the duodenum was synchronized with the antral slow waves (Allen et al 1964). This phenomenon can be explained by the results of Bortoff & Weg (1965) and Bortoff & Davis (1968) who found that 'antral slow waves spread electrotonically across the gastroduodenal junction and into the proximal duodenum where they periodically augment the depolarizations produced by the duodenal waves themselves' (Bortoff, 1975). Besides this transmission of gastric slow waves contractions of the duodenum may also be stimulated by reflexes or by the evacuated gastric chymus.…”
Section: Discussionmentioning
confidence: 99%
“…This is suggested by the lack of innervation of some portions of the digestive tract, including, strikingly, the main digestive and absorptive portion of the midgut (37). Myogenic transmission of electrical activity in the absence of innervation has been demonstrated across the gastroduodenal junction of cats, dogs, and primates (14). The few studies of peristaltic regulation in Drosophila have concerned the effects of neuropeptides, such as dromyosuppressin, allatostatin-C, and drosulfakinin, on ex vivo intestinal preparations (92,138,142).…”
Section: Intestinal and Nonintestinal Roles Of Enteric Neuronsmentioning
confidence: 99%